Peer Recruitment Strategies for Female Sex Workers Not Engaged in HIV Prevention and Treatment Services in Côte d'Ivoire: Program Data Analysis - Olawore, Oluwasolape; Astatke, Hibist; Lillie, Tiffany; Persaud, Navindra; Lyons, Carrie; Kamali, Didier; Wilcher, Rose; Baral, Stefan (JMIR Publications, 2020)
BackgroundIn the context of the mostly generalized HIV epidemic in Côte d'Ivoire, key populations bear a higher burden of HIV than that borne by the general reproductive-aged population. Mathematical models have demonstrated the significant potential impact and cost-effectiveness of improving the coverage of HIV prevention and treatment services for key populations in Côte d'Ivoire. However, in 2019, coverage of these services remained limited by multiple intersecting stigmas affecting key populations, necessitating the study of innovative implementation strategies to better meet the needs of those most marginalized. Here, we leverage programmatic data to compare the effectiveness of the enhanced and traditional peer outreach approaches in reaching and providing community HIV testing to female sex workers not readily engaged in HIV prevention and treatment services in Côte d'Ivoire. ObjectiveThe aim of this study was to describe the characteristics of female sex workers reached by the LINKAGES project in Côte d'Ivoire with enhanced peer outreach and traditional peer outreach and to compare HIV-related outcomes between the women reached by both strategies. MethodsDeidentified routine programmatic data collected as part of LINKAGES Côte d'Ivoire between October 2017 and April 2018 were used in these analyses. Demographic characteristics and HIV indicators including HIV testing history, HIV case-finding, linkage to HIV treatment, and treatment initiation were assessed using descriptive statistics. Differences in these indicators were compared by outreach strategy using Pearson chi-square tests. ResultsThere were 9761 women reached with enhanced peer outreach and routine peer outreach included in these analyses. The overall case-finding rate in the sample was 7.8% (698/8851). Compared with women reached by routine outreach, those reached by enhanced peer outreach were more likely to have previously been tested for HIV (enhanced: 1695/2509, 67.6%; routine: 4302/7252, 60.0%; χ21=43.8; P=.001). The enhanced peer outreach approach was associated with a higher HIV case-finding rate (enhanced: 269/2507 10.7%; routine: 429/6344, 6.8%; χ21=32.3; P=.001), higher proportion of linkage to treatment (enhanced: 258/269, 95.9%; routine: 306/429, 71.3%; χ21=64.4; P=.001), and higher proportion of treatment initiation (enhanced: 212/269, 78.8%; routine: 315/429, 73.3%; χ21=2.6; P=.11). Women reached by both approaches were categorized as high risk for HIV-related behaviors such as condomless sex and number of sex acts in the previous week. ConclusionsThese analyses suggest that the novel peer-referral strategy, the enhanced peer outreach approach, was effective in reaching female sex workeres in Côte d'Ivoire with demonstrated acquisition risks for HIV and who had not been effectively engaged by routine outreach approaches. Scaling up novel strategies such as enhanced peer outreach in the context of differentiated service models may be needed to optimize HIV prevention and treatment outcomes for key populations in Côte d'Ivoire.